Avaliação do tratamento adjuvante com tamoxifeno em mulheres com câncer de mama - Alencar, Victor Hugo Medeiros (2006)
Breast cancer is a disease that was described many years ago and has been documented, for the first time, by Imhotep, physician, astrologer and Egyptian architect, born in 2.650 before Christ (b.C.), who recommended, at that time, as a way of treatment, cauterization of the diseased tissue. Tamoxifen is the drug more prescribed in the treatment of breast cancer. It’s use is mainly in the adjuvant modality, in pre or post menopaused patients positive estrogen and/or progesteron receptors. It’s used in the treatment of locally advanced and metastatic disease and in smaller proportion in patients with formal contraindication of surgery or that refuse to submit this treatment modality. In the neoadjuvancy it is just used in clinical research. The tamoxifen also reduces in the adjuvant modality during five years, the probability of recurrence in 47% and deaths caused by breast cancer in 26% and the two main side effects, in spite of rare, are the increase of the prevalence of endometrial cancer and of thromboembolic phenomenas. This study had as main objective to evaluate the patients, breast cancer bearers, in the Institute of Cancer of Ceará, treated with tamoxifen in the adjuvant form in the period of 1993 to 1996 regarding the main benefits and side effects, as well as survival analysis. Seven hundred forty-two patients’prontuaries were analyzed in respect to the demographic datas, age, menopausal status, clinical and pathological staging, dosage of estrogen and/or progesterone receptors, cases of endometrial cancer, main local metastasis, modality of surgical treatment, radiotherapy and chemotherapy, death causes, histological type, status of the axillary lymph nodes and survival analysis in agreement with the staging. We concluded that most of the data is in agreement with the literature and that the demage of the analysis was resulting from the quality accomplished found in the prontuaries. Also, doctors should be more and more stimulated to document, in a clear and readable way, the largest number of possible information, not just the positive ones, but all those that more frequently can have relationships with the use of any prescribed medicine.